Pengembangan Modul Berbasis Pemecahan Masalah Soal Cerita untuk Meningkatkan Kemampuan Literasi Matematika Siswa Kelas IV SD - Elli Nurdahwati; Agus Susanta; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to produce a story problem-solving-based module to improve the math literacy skills of fourth-grade students at SDN Mukomuko City. This research method is the Research and Development (R&D) method by modifying the 4D model. However, this research only reached the development stage, while the deployment stage could not be carried out due to time constraints, so this stage was not discussed in depth. Validation was carried out by material experts, linguists, and design experts. The modules developed were rated by the students and teachers of SDN 11 Kota Mukomuko. It was also tested on a limited basis at SD 4 Kota Mukomuko. Data analysis techniques using qualitative and quantitative descriptive analysis. The results of expert validation were tested with the interrater reliability test to see agreement between raters. The validation results showed the value of Aiken's V coefficient of each feasibility item for material experts, linguists, and design experts. stated to have high validity. Furthermore, the reliability of the material feasibility was tested, namely, at 72%, language feasibility at 80%, and design feasibility at 64%, and expert comments that the depth of the description was in accordance with the level of student development, paying attention to statements related to language, such as spelling, grammar, writing must be appropriate and use capital letters. the standard size and then the color of the text with a background color that lacks contrast. The product of the development of word problems problem-solving modules to improve students' mathematical literacy skills is very good for use by fourth-grade elementary school students.